2018
DOI: 10.1007/s12185-018-2527-y
|View full text |Cite
|
Sign up to set email alerts
|

KIF20A, highly expressed in immature hematopoietic cells, supports the growth of HL60 cell line

Abstract: A microtubule-associated motor protein, kinesin-like family member 20A (KIF20A; also called MKlp2) is required for cytokinesis and contributes to intracellular vesicular trafficking. KIF20A plays a critical role in the development of several cancers, but its role in blood cells and hematological malignancies have not been studied. In the present study, we focused on the role of KIF20A in hematopoietic cells and possible involvement in myeloid neoplasms. We found that human leukemia cell lines and normal bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…12,13 Cancer cells overexpressed KIF20A can be recognized by hosts to initiate immune response, thereby KIF20-derived peptides could be used as a novel immunotherapy agent. 5,14 Several clinical trials using KIF20A vaccine had been performed. 15,16 However, no data are available to date about the role of KIF20A in NSCLC.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…12,13 Cancer cells overexpressed KIF20A can be recognized by hosts to initiate immune response, thereby KIF20-derived peptides could be used as a novel immunotherapy agent. 5,14 Several clinical trials using KIF20A vaccine had been performed. 15,16 However, no data are available to date about the role of KIF20A in NSCLC.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“… 99 Kinesin family member 20A (KIF20A) is required during mitosis for the final step of cytokinesis. 100 , 101 Studies have found that high expression of KIF20A is correlated with progression or poor prognosis of many types of cancers. 102 104 Furthermore, KIF20A is aberrantly expressed in HCC tissues and its expression may be associated with poor OS.…”
Section: Discussionmentioning
confidence: 99%
“…KIF20A, also known as mitotic kinesin-like protein 2 (MKlp2) or rabkinesin6 (RAB6KIFL), is a kinesin-6 family 10 microtubule plus-end directed motor that is also necessary in the exit of mitosis for the final step of cytokinesis ( 25 ). KIF20A is found in the central spindle during mitosis, whose phosphorylation is necessary for cytoplasmic division ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of KIF20A is linked to the onset, progression, and prognosis of different cancers. Recent researches have reported that KIF20A was upregulated in esophageal squamous cell carcinoma ( 28 ), lung adenocarcinoma ( 29 ), prostate cancer ( 30 ), cervical cancer ( 31 ), colorectal cancer ( 32 ), non-small cell lung cancer ( 33 ), gastric cancer ( 34 ), bladder cancer ( 35 ), renal clear cell carcinoma ( 36 ), breast cancer ( 37 ), hepatocellular carcinoma ( 38 ), nasopharyngeal carcinoma ( 39 ), ovarian cancer ( 40 ), leukemia ( 25 ), glioma ( 41 ), and soft tissue sarcoma ( 42 ). This is consistent with our analysis in the GEPIA online database.…”
Section: Discussionmentioning
confidence: 99%